Manipulation of ferrofluid droplets using planar coils - Nguyen, Nam-Trung (2012)
In this letter, the authors report a system for magnetic manipulation of ferrofluid droplets and their dynamic behavior. The magnetic field was generated by an array of planar coils, which were fabricated on a double-sided printed circuit board (PCB). The permanent magnetic moment of the ferrofluid droplet was created by the field of a pair of permanent magnets. The motion of the ferrofluid droplet is further aligned in a virtual channel formed by a pair of planar coils. Two other planar coils on the other side of the PCB drive the droplet along this virtual channel. The direction of the droplet motion can be controlled by reversing the electric current in the coils. Based on the experimental results, a larger droplet size, a lower viscosity of the surrounding medium, and a higher electric current will increase the droplet velocity.